Fun Learning Innovation as an Effective Strategy in Increasing Students’ Learning Engagement in Non-formal Education - Fakhrunnisa, Resya; Karsiwan, Wawan; Fajartriani, Tia; Kadfi, Canra Muhammad; Pelita, Pepi Januar (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to examine the effectiveness of the fun learning strategy in enhancing student engagement, motivation, and academic achievement within non-formal education settings, particularly tutoring centers. A quantitative approach was employed using a one-group pretest-posttest experimental design. The research subjects consisted of 25 elementary school students enrolled in a local tutoring program. Data were collected through pretest and posttest assessments, learning motivation questionnaires, student engagement observation sheets, and supporting interviews. The results showed a significant increase in students' average scores from pretest (55.4) to posttest (78.4), alongside a rise in learning motivation scores from 3.18 to 4.5. Student engagement during the learning process was also notably high, with an average observation score of 4.55 out of 5. These findings support previous literature and demonstrate that fun learning is an effective instructional strategy in non-formal educational contexts. The study concludes that fun learning can serve as a relevant and applicable pedagogical approach to improve learning quality in tutoring institutions. It also contributes to the development of active and enjoyable learning models beyond the formal school environment.